TINJAUAN KRIMINOLOGI TERHADAP PENJUAL KORAN DENGAN BERSERAGAM SEKOLAH (Studi Di Lampu Lalu Lintas Simpang Tiga Tengku Bey Kota Pekanbaru) - Windy Tahnia (UIR PRESS, 2020)
The purpose of this study was to determine the factors underlying newspaper sellers who did not attend school, but used school uniforms when selling newspapers. As well as this study aims to provide knowledge that children are not only able to become objects but also have the potential to become subjects. The research method used is qualitative with the type of phenomenological research. The research location is the Simpang Tiga Tengku Bey Traffic Lights in Pekanbaru City. The conclusion of this study is VI is the subject of deviant behavior with school uniform symbols as a mode to attract community empathy.